Gender Stereotypes in Nigerian Advertising: A Critical Discourse - Akpan, Uwem Asuquo; Umoren, Philomena; Nwokeocha, Ifeanyi Martins (International Journal of Global Sustainable Research, 2024)
The study explores gender stereotypes in Nigerian advertising, focusing on their impact on societal perceptions, attitudes, and consumer buying behaviors. It uses feminist and social constructionism theory to provide a critical discourse on the issue. The study concludes that advertisers and marketers play a crucial role in influencing societal attitudes and perceptions through their campaigns. It suggests that advertisers should actively seek to represent a diverse range of gender identities, reflecting the complexity and diversity of Nigerian society. This can include showcasing individuals from different gender identities, backgrounds, and experiences, contributing to a more inclusive and representative portrayal of gender in advertising.